Managing Services, Resources and Activities in Product Companies: Does Supply Chain Management Moderates? - Reschiwati Reschiwati; Arum Indrasari (International Journal of Supply Chain Management, 2020)
The aim linked with the current article is to examine the impact of services offering, resource base and activity system business on the companies benefit of the transport companies in Indonesia. The aim also consists of analyzing the moderating role of supply chain management among the links of services offering, resource base and activity system business on the companies benefit of the transport companies in Indonesia. The data has been gathered from the employees of transport companies by using questionnaires while the collected data has been analyzed by using smart-PLS. The results indicated that all the predictors such as services offering, resource base and activity system business have a positive association with companies benefit from the transport companies in Indonesia. The results also exposed that the supply chain positively moderated among the links of services offering and companies benefit from the transport companies in Indonesia. These findings provide the guidelines to the upcoming studies along with the policymakers while investigating and formulating the policies related to the supply chain and companies benefits.